Production quality and safety management in the corporate-type integrated structures in the agro-industrial complex - Bogdanova Irina; Dymchenko Olga (E3S Web of Conferences, 2020)
The article (paper) presents questions connected with the abilities of corporate-type integrated structures in the imports phase-out problems solving applied to the agro-industrial production. The paper deals with the advantages of the corporate-type integrated systems functioning, describes the profits from its functioning for the national economy in general. There offered management tools for the quality of production in the corporate-type integrated systems, and the indicative-planning elements use among other factors. There presented the implementation scheme of cycle process of production quality management and the algorithm of the analysis and control of production quality and safety control of the corporate-type integrated structures, functioning in the agro-industrial complex.